2000
DOI: 10.1021/np000327d
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Constituents from Hedyotis diffusa

Abstract: In a bioassay-guided search for neuroprotective compounds from medicinal plants, a MeOH extract of whole plants of Hedoytis diffusa yielded five flavonol glycosides, kaempferol 3-O-[2-O-(6-O-E-feruloyl)-beta-D-glucopyranosyl]-beta-D-galactopyranoside (1), quercetin 3-O-[2-O-(6-O-E-feruloyl)-beta-D-glucopyranosyl]-beta-D-galactopyranoside (2), quercetin 3-O-[2-O-(6-O-E-feruloyl)-beta-D-glucopyranosyl]-beta-D-glucopyranoside (3), kaempferol 3-O-(2-O-beta-D-glucopyranosyl)-beta-D-galactopyranoside (4), and querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 18 publications
3
56
1
Order By: Relevance
“…12) Kaempferol had earlier been shown to afford efficient neuroprotection against several apoptosis and necrosis-inducing insults, such as oxidized low-density lipoproteins 13,14) and L-glutamate. 15,16) Ishige et al 15) demonstrated that kaempferol efficiently blocked the increase in ROS associated with the oxidative stress caused by glutamate in the mouse hippocampal cell line HT-22. Filomeni et al 6) demonstrated that kaempferol exerted a strong and prolonged protective effect against rotenone toxicity, which was a classical toxin inducing PD.…”
mentioning
confidence: 99%
“…12) Kaempferol had earlier been shown to afford efficient neuroprotection against several apoptosis and necrosis-inducing insults, such as oxidized low-density lipoproteins 13,14) and L-glutamate. 15,16) Ishige et al 15) demonstrated that kaempferol efficiently blocked the increase in ROS associated with the oxidative stress caused by glutamate in the mouse hippocampal cell line HT-22. Filomeni et al 6) demonstrated that kaempferol exerted a strong and prolonged protective effect against rotenone toxicity, which was a classical toxin inducing PD.…”
mentioning
confidence: 99%
“…4,5,7) Compound 3 was obtained as slightly yellow powder; mp 59-60°C; l max 312 (e 3365) (MeOH). The molecular formula was determined to be C 27 …”
Section: Resultsmentioning
confidence: 99%
“…Compare with those spectral data of the known compound 2 (Tables 3, 4), compound 3 was determined to have an additional methoxy group signal. 4,5,7) Therefore, the structure of 3 is de- No. termined to be E-6-O-p-coumaroyl scandoside methyl ester-10-methyl ether which was not reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…A reaction mixture (20 ml) containing 50 mM Tris-HCl (pH 8.3), 30 mM NaCl, 10 mM MgCl 2 , 5 mM DTT, 1.25 mg/ml (ca. 16 nM) poly(rA).oligo(dT) [12][13][14][15][16][17][18] as a template primer, 250 nM dTTP, 100 nM [methyl-3 H]dTTP (18.5 MBq/ml), 0.01 U/ml of RT, and 1.0 ml of a test compound dissolved in dimethyl sulfoxide (DMSO) (final concentration of 5%) was incubated at 37°C for 1 h. A control reaction was done under the same conditions without adding the test compound. The reaction was terminated by the addition of 20 ml of 0.02 M EDTA.…”
Section: Isolation Of Compounds 1-14 From the Leaves Of T Peruvianamentioning
confidence: 99%
“…As regards the bioactivities of flavonol glycosides, quercetin and kaempferol 3-O-[(6-feruloyl)-glucopyranosyl-galactopyranoside] were reported to show neuroprotective activity in primary cultures of rat cortical cells damaged by L-glutamate, 18) whereas quercetin 3-O-[(6-feruloyl)-galactopyranoside] exhibited anti-superoxide production, 19) and anticomplement effects. 20) Feruloyl and sinapoyl glycosides showed radical scavenging activities against a 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and inhibitory activity against the oxidation of linoleic acid.…”
mentioning
confidence: 99%